2006
DOI: 10.17796/jcpd.30.1.d3n7k5147r3ru571
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience Associated with Attention – Deficit / Hyperactivity Disorder

Abstract: The purpose of this cross-sectional study was to examine whether children with attention-deficit / hyperactivity disorder (ADHD) had a total caries experience that was equivalent to children without the disorder. Methods: The test sample included children ages 6 to 10 years old diagnosed with ADHD by physicians at Duke University Medical Center. The control group also included healthy children 6 to 10 years old without the diagnosis of ADHD.A visual dental exam for caries was performed and a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
61
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 10 publications
7
61
3
4
Order By: Relevance
“…Our findings are the most similar to those of Hidas et al [2011], who reported that nonmedicated children with ADHD had marginally significantly (p = 0.08) fewer carious lesions compared with control children with the effect size for the difference (r = -0.24; p = 0.08) very consistent with those that we report. In contrast, Grooms et al [2005] did not find a significant difference in primary tooth caries in nonmedicated children with ADHD compared with control children (r = -0.06). Medication data were not collected in the present sample; however, participants were drawn from an extremely impoverished population with very poor access to health care.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our findings are the most similar to those of Hidas et al [2011], who reported that nonmedicated children with ADHD had marginally significantly (p = 0.08) fewer carious lesions compared with control children with the effect size for the difference (r = -0.24; p = 0.08) very consistent with those that we report. In contrast, Grooms et al [2005] did not find a significant difference in primary tooth caries in nonmedicated children with ADHD compared with control children (r = -0.06). Medication data were not collected in the present sample; however, participants were drawn from an extremely impoverished population with very poor access to health care.…”
Section: Discussioncontrasting
confidence: 61%
“…Accordingly, we are certain that the vast majority of study children, if not all, were not medicated. Taking our findings together with those of Hidas et al [2011] and Grooms et al [2005], it seems possible that medication changes the association of externalizing problems and caries, with positive associations a byproduct of psychiatric medication. Children on medication may experience changes in appetite leading to increased sucrose intake (perhaps due to increased parental leniency in the face of the side effect of appetite suppression), thus explaining increased caries rates in children with externalizing behavioral problems.…”
Section: Discussionmentioning
confidence: 53%
“…Bazı araştırıcılar, çürük, kayıp, dolgulu dişler (DMFT)/dmft skorlarının DEHB'li çocuklarda daha fazla olduğunu bildirirken (11,12,43,47), kimi araştırıcılar kavitasyonlu çürük lezyonları ve diş çürüğü sonuçları açısından, DEHB'li çocukların sağlıklı çocuklarla benzer durumda olduklarını tespit etmişlerdir (28,42,44,48).…”
Section: Dikkat Eksikliği Ve Hiperaktivite Bozukluğu Diş çüRüğü Oluşuunclassified
“…ABD'de 6-10 yaş aralığındaki DEHB'li çocukların daha fazla mine çürüğüne sahip olduğu bildirilmiştir (12). Yeni Zellanda'da yapılan bir araştırma sonucunda, DEHB olan çocukların DMFT skorlarının 5'ten büyük olma riskinin daha yüksek olduğu ve 11-13 yaş grubunda DEHB'nin yüksek diş çürüğü aktivitesi için bir risk faktörü olduğu bildirilmiştir (43).…”
Section: Dikkat Eksikliği Ve Hiperaktivite Bozukluğu Diş çüRüğü Oluşuunclassified
See 1 more Smart Citation